Hubungan Rasio Keuangan Dan Harga Saham - Asadanie, Nabila Khoirunnisa (Politeknik Ganesha Medan, 2024)
Investors use financial ratios to analyze companies by comparing the financial ratios of a company with similar companies so as to provide convenience and speed in the decision making process. This study aims to examine the effect of the Current Ratio, ROE, DER, EPS and NPM on stock prices. CR, ROE, DER, EPS and NPM have an important role on stock prices. This study uses secondary data from the annual financial reports of LQ45 companies listed on the Indonesia Stock Exchange for the 2020-2022 period using a purposive sampling method. There were 78 observations that filled the sample. This study uses multiple linear regression analysis method. The results showed that CR, ROE, EPS and NPM have a significant effect on stock prices and DER has an insignificant effect on stock prices. While simultaneously, CR, ROE DER, EPS and NPM affect stock prices.